Direct examination of Si atoms spatial distribution and clustering in GaAs thin films with atom probe tomography. (August 2018) - Beainy, Georges; Alcotte, Reynald; Bassani, Franck; Martin, Mickaël; Grenier, Adeline; Baron, Thierry; Barnes, Jean-Paul
Abstract: In this contribution, we report on the Si atoms spatial distribution via Atom Probe Tomography (APT) in Si-doped GaAs thin films grown by MOCVD. As a result, we clearly identify the presence of Si precipitates occurring with increasing Si content in the layers. Using ToF-SIMS characterizations, we have been able to highlight the increasing evolution of the silicon content in the material as a function of silicon flux while that of the charge carriers studied by Hall effect decreases. Thus, this degradation of the electrical properties was directly linked to the observed clusters by APT. Graphical abstract: Unlabelled Image